The public eye - Shaffer, Paul.; Wallis, Hal. B.; Reed, Carol; Farrow, Mia.; Topol; Jayston, Michael ([United States] Universal, 1971)
Charles (Michael Jayston) hires a detective, Chrisoforou, (Topol) because he suspects that his wife Belinda (Mia Farrow) is having an affair but Charles didn't quite expect who the "lover" would be.
VHS
"From the play 'The Public eye' by Paul Shaffer."
Associate producer, Paul Nathan.
Mia Farrow, Topol, Michael Jayston.